Case-Designed Lesson Plans as a Means of Assessing Methodological Competency of Pedagogical Students and Primary School Teachers - N. N. Demeneva; O. V. Kolesova (Russian State Vocational Pedagogical University, 2018)
Introduction. The implementation of competency-based approach in the university requires the development of evaluation tools, which contribute to assessing the formation of professional competencies. Diagnostic materials should reflect the real school practice, the experience of teachers, as well as the existing methodological problems and difficulties when organising the activities of teachers.The aim of the research was to assess the effectiveness of case-note as an assessment tool, which allows us to judge the methodological competency both of a university graduate and a practising teacher.Methodology and research methods. The research was carried out employing activity and competency-based approaches related to the application of methods of modelling and comparative analysis.Results and scientific novelty. As a means of a diagnostic methodology, a case-designed lesson plan presented by the authors combines the characteristics of a traditional lesson plan and a case-structured assignment. The features of the case-designed lesson plan and its content specificity were thoroughly analysed; specific examples were provided.The approbation of methodology was carried out among the students enrolled in "Psychology and Pedagogy of Primary Education" direction and primary school teachers, who attended advanced training courses. The results of performing tasks in Mathematics case-designed lesson plans were analysed by different categories of examinees, who participated in the research. The indicators determined in the groups of teachers were ranged according to the qualification category and work experience of teachers. Problems, typical challenges and mistakes made were commented on. On the basis of comparing the data obtained in groups of teachers and students, it was concluded that a case-designed lesson plan can serve as an effective tool for diagnosing the methodological readiness of future teachers and practising teachers for professional work. The recommendations on drafting case-designed lesson plans were proposed.Practical significance. The materials of the research can be useful for university teacher-methodologists when developing tools for diagnosing graduates' readiness for professional pedagogical activity. Case-designed lesson plans can be used as a didactic material in the course of practical training of university students or further training of teachers.